Differences in Outcomes Over Time With Exclusive Enteral Nutrition Compared With Steroids in Children With Mild to Moderate Crohn's Disease: Results From the GROWTH CD Study. (27th March 2017) - Cohen-Dolev, Noa; Sladek, Malgorata; Hussey, Seamus; Turner, Dan; Veres, Gabor; Koletzko, Sibylle; Martin de Carpi, Javier; Staiano, Annamaria; Shaoul, Ron; Lionetti, Paolo; Amil Dias, Jorge; Paerregaard, Anders; et al.
Abstract: Background: Exclusive enteral nutrition [EEN] and corticosteroids [CS] induce similar rates of remission in mild to moderate paediatric Crohn's disease [CD], but differ with regard to mucosal healing. Our goal was to evaluate if EEN at diagnosis was superior to CS for improving long-term outcomes. Methods: We prospectively followed newly diagnosed children aged < 17 years, with mild to moderate CD at baseline, for 2 years in the GROWTH CD study. Patients were evaluated at baseline and at 8, 12, 78, and 104 weeks. Remission, relapses, complications [fibrostenotic disease, penetrating disease, and active perianal disease] and growth were recorded throughout the study. A propensity score analysis was performed. Results: A total of 147 children [mean age 12.9 ± 3.2 years], treated by EEN [ n = 60] or CS [ n = 87] were included. New complications developed in 13.7% of CS [12/87] versus 11.6% of EEN [7/60], p = 0.29. Remission was achieved in 41/87 [47%] in CS and 38/60 [63%] EEN, p = 0.036. Median time to relapse did not differ [14.4 ± 1 months with CS, 16.05 ± 1.1 EEN, p = 0.28]. Mean height Z scores decreased from Week 0 to Week 78 with CS [-0.34 ± 1.1 to -0.51 ± 1.2, p = 0.01], but not with EEN [-0.32 ± 1.1 to -0.22 ± 0.9, p = 0.56]. In a propensity score analysis, EEN was superior to CS for inducing remission [ p = 0.05] and trended to superiority for height Z score [ p = 0.055]. Conclusions: Use of EEN was associated with higher remission rates and a trend toward better growth but with similar relapse and complication rates in new-onset mild to moderate paediatric CD.